The Effect of MELD Score on Survival in Patients with Living Donor Liver Transplantation - Yilmaz, Mehmet; Akbulut, Sami; Karabulut, Koray; Sakcak, Ibrahim; Yilmaz, Sezai (Wiley-Blackwell, 2012)
[Abstract Not Available]
18th Annual International Congress on ILTS -- MAY 16-19, 2012 -- San Francisco, CA